Meet the Expert Grady Booch on Software Architecture in the Age of AI - Booch, Grady (O'Reilly Media, Inc., 2020)
AI is a kind of software-intensive system that reasons and learns. As such, while AI is still just software, it differs from traditional systems in ways both subtle and material. In this Meet the Expert with Grady Booch, learn how architecting an AI system is different and how introducing AI components to non-AI systems impacts the architecture, process, and infrastructure of development. Recorded on May 4, 2020. See the original event page for resources for further learning or watch recordings of past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.